Extremity Massage with Aromatherapy Lemongrass Lowers Blood Pressure Hypertension Patients - Ethyca Sari; Aristina Halawa (Sarana Ilmu Indonesia (salnesia), 2022)
Hypertension is caused by various factors including severe stress and an unhealthy lifestyle. Various ways are done to lower blood pressure, one of which is lemongrass aromatherapy combined with massage. The purpose of this study was to determine the effect of extremity massage using lemongrass aromatherapy on blood pressure in patients with hypertension. This study uses a pre-experimental research design with one group pre-post test design. The population in this study were 15 respondents with hypertension and a total sample of 14 respondents using the Non-Probability Sampling (Purposive Sampling) technique. The data was collected using observation before and after the action and then statistically tested using the wilcoxon test. From the results of the study, respondents before the extremity massage were mostly stage I hypertension by 57%, and after the extremity massage were mostly normal by 64%. So that there is an effect of extremity massage with lemongrass aromatherapy to reduce blood pressure in hypertensive patients with p = 0,000. Therefore, it is hoped that extremity massage using lemongrass aromatherapy can be used as an alternative treatment to lower blood pressure, especially for people with hypertension.